(untitled) (Research, Society and Development, 2022)
According to the World Health Organization (WHO), breastfeeding is the most important food in a child’s life, and it should be offered within 1 h after birth. It has all the nutrients necessary for the child’s development, and can even prevent the onset of cardiovascular diseases throughout life, such as; obesity, diabetes, hypertension and others, in addition to these cardiovascular pathologies, others can also be prevented, such as food and respiratory allergies. Studies show that breastfeeding can prevent around 13% of deaths in children under 5 years old worldwide. Human milk varies in its composition throughout infancy, providing infants with specific substances suitable for each age and situation, and its composition contains up to 88% water and there is no supply of water, juices or even teas. The introduction of complementary foods must be done at the right time, so that the child is already prepared to receive foods other than breast milk, so it must be done gradually, respecting the child’s limits. Already the introduction of food before six months can compromise development and extend throughout life, leaving the child more vulnerable to infections, diarrhea, malnutrition.